Financing Structures for CDM Projects in India and Capacity Building Options for EU-Indo Collaboration - Matthias Krey; Axel Michaelowa; Vinay Deodhar (Hamburg Institute of International Economics (HWWA), 2003)
The Clean Development Mechanism (CDM) under the Kyoto Protocol to the UN Framework Convention on Climate Change (UNFCCC) enables industrialized countries to meet a part of their emission reduction requirements through purchase of emission reduction credits from projects in developing countries. Various studies have concluded that India is likely to be one of the major countries supplying such projects. However, in order that a large number of high-quality CDM projects is developed and result in Certified Emission Reductions as specified by the international CDM Executive Board, the institutional set up in the Indian finance sector has to be suitably geared up. So far, banks and financial institutions have not developed procedures for efficient financing of CDM projects. A necessary condition for an in-depth involvement of the financial sector is the development of transparent and effective approval rules by regulators both on the central and state level as well as improved project development capacity of the private sector. Then conventional and novel financing instruments such as project finance for large projects, Special Purpose Vehicles, CDM funds or CDM bonds couldbecome attractive to banks. Such a set up helps in reducing the permit credit risks and political risks considerably. This discussion paper describes the current status of the CDM stakeholders in India, assesses risk perspectives of CDM projects and provides suggestions for approaches these stakeholders may adopt in order that projects from Indian promoters are able to capture a sizeable share of emerging competitive CDM market. It also defines options for capacity building support from EU countries.
Keywords: O13; Q25; 330; International Climate Policy; CDM; Financial Institutions; India; Klimaschutz; Internationale Umweltpolitik; Clean Development Mechanism; Entwicklungsprojekt; Indien; EU-Staaten